Kaolin in pharmaceutical preparations: a review - Rezkia Azka Kamila (Universitas Islam Indonesia, 2021)
Background: Kaolin is a clay mineral with Al2Si2O5(OH)4 structure which can be found in sedimentary rocks also known as clay stones. Kaolin consists of clay materials such as quartz, illite, smectite, and hematite, with the largest constituent component being kaolinite. Kaolin is one of the most common minerals with an abundant presence in the earth's crust compared to other minerals, especially in Indonesia. In the pharmaceutical sector, this clay mineral is widely used in Indonesia. Kaolin is known to be a good adsorbent and has good physical, chemical, and surface physicochemical properties. Objective: This review article aims to provide information about the uses of kaolin in the pharmaceutical industry.Methods: This review article was written by conducting a literature search study method in the PubMed, ScienceDirect, and Google Scholar databases.Results: In the pharmaceutical field, kaolin is used as an excipient in various types of medicinal preparations, one of which is as a suspension agent because of its ability to stabilize suspensions in a deflocculated state as an emulsifying agent, crushing agent, filling agent, and drug carrier. As an active substance, kaolin is widely used because it has a therapeutic activity. In the cosmetic industry, kaolin can be administered in a variety of topical dosage forms which act as skin protective agents or sunscreens.Conclusion: Based on the results of the review, it was found that kaolin, with its abundant presence on earth and its great potential in the pharmaceutical field, is used as an active medicinal substance, excipient ingredient, and in the cosmetic field as a sunscreen.Keywords: Kaolin, excipient, active pharmaceutical ingredient, cosmeticsIntisariLatar belakang: Kaolin merupakan mineral dengan struktur Al2Si2O5(OH)4 yang dapat ditemukan pada bebatuan sedimen yang juga dikenal sebagai batu lempung. Kaolin terdiri dari berbagai macam mineral lain sebagai penyusunnya seperti kuarsa, illit, smektit, hematit, dan komponen mineral penyusun yang paling besar adalah kaolinit. Kaolin adalah salah satu mineral paling umum dengan keberadaannya yang melimpah di kerak bumi dibandingkan dengan mineral lain khususnya di Indonesia dapat dimanfaatkan dalam bidang farmasi. Kaolin dikenal sebagai bahan adsorben yang baik dan juga memiliki sifat fisika, kimia, dan sifat fisikokimia permukaan yang baik.Tujuan: Ulasan artikel ini bertujuan untuk memberikan informasi mengenai kaolin di bidang kefarmasian. Metode: Ulasan artikel ini ditulis dengan melakukan metode studi penelusuran literatur dalam database Pubmed, Science Direct, dan Google Scholar.Hasil: Dalam bidang kefarmasian, kaolin digunakan sebagai bahan eksipien berbagai macam jenis sediaan obat salah satunya adalah digunakan sebagai bahan pensuspensi karena kemampuannya untuk menstabilkan suspensi dalam keadaan deflokulasi, sebagai agen pengemulsi, penghancur, pengisi, dan pembawa obat. Sebagai zat aktif kaolin banyak digunakan karena memilki aktivitas terapeutik. Dalam industri kosmetik kaolin dapat diberikan dalam berbagai macam bentuk sediaan topikal yang berfungsi sebagai agen pelindung kulit atau tabir surya.Kesimpulan: Berdasarkan hasil ulasan, didapatkan bahwa kaolin dengan keberadaan yang melimpah di bumi dan potensinya yang besar dalam bidang farmasi, diyakini memiliki peran besar dalam pengembangan di industri farmasi dan kosmetik.Kata kunci : Kaolin, Eksipien, Zat Aktif, Kosmetik